Analisis Pengaruh Belanja Modal Infrastruktur terhadap Tingkat Pengangguran Terbuka Melalui Pertumbuhan Ekonomi sebagai Variabel Intervening di Kabupaten Kutai Kartanegara - Faisyal Riza; Juliansyah Roy; Diana Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of Regional Infrastructure Capital Expenditure disaggregated into Capital Expenditure on Equipment and Machinery (X1), Buildings (X2), and Roads, Networks, and Irrigation (X3) on the Open Unemployment Rate (Y2) through Non-Mining Economic Growth (Y1) as an intervening variable. The research employs an explanatory associative quantitative method with a Path Analysis approach. Fifteen years of annual time-series secondary data (2010–2024) were collected from Statistics Indonesia (BPS) and the Regional Financial and Asset Management Agency (BPKAD) of Kutai Kartanegara Regency. The regression results indicate that only Capital Expenditure on Buildings has a positive and significant effect on economic growth. Conversely, economic growth has no significant effect on the open unemployment rate, which mathematically invalidates the mediation function in the Sobel Test. This condition provides empirical confirmation of the jobless growth anomaly in a resource-rich region. Another crucial finding shows that Capital Expenditure on Roads, Networks, and Irrigation has a direct, positive, and significant effect on increasing open unemployment, driven by the massive migration influx of job seekers into the buffer zone of the Nusantara Capital City (IKN) that excludes the local workforce. The Government of Kutai Kartanegara Regency is recommended to re-engineer infrastructure procurement contract clauses to mandate local labor absorption and accelerate competence certification for the domestic workforce.